Kualitas Pertumbuhan Tanaman Kelor (Moringa oleifera) Terhadap Dosis Pupuk Organik Fermentasi Berbeda - Zikri, Ahmad; Syarifuddin, Nursyam Andi; Riyadhi, Muhammad (www.ulm.ac.id, 2025)
Ultisol soil is characterized by very low organic matter content. The application offermented organic fertilizer can affect the growth of plants grown in ultisol soil. Thisstudy aims to determine the effect of the doses of fermented organic fertilizer on thegrowth of moringa seedling plants planted in ultisol soil. The study used a completelyrandomized design with five treatments and eight replications, using five levels offertilizer application: D0 (basic fertilizer/control), D1 (basic fertilizer + fermented organicfertilizer at 10 tons/ha), D2 (basic fertilizer + fermented organic fertilizer at 20 tons/ha),D3 (basic fertilizer + fermented organic fertilizer at 30 tons/ha), and D4 (basic fertilizer+ fermented organic fertilizer at 40 tons/ha). The observed variables included the time ofsprout emergence, the number of sprouts, plant height, and fresh leaf production. Dataanalysis was performed using analysis of variance, and if the treatment had a significanteffect, it was followed by the Least Significant Difference (LSD) test. Data analysis wasassisted by using SPSS Ver. 21 software. The results showed that none of the treatmentshad a significant effect (P>0.05), but there was a tendency for earlier sprout emergence(10.50 days) and more sprouts (6.13 sprouts) in the D2 treatment. In contrast, the slowestsprout emergence (14.00 days) and fewer sprouts (3.88 sprouts) in the D3 treatment.